Empowering Chicken Farmers in Talok Village: Strategies for Food Security and Mitigating Environmental Health Impacts - Erna Agustin Sukmandari Sukmandari; Rosmalia; Toto Sudibyo (Universitas Veteran Bangun Nusantara, 2026)
ABSTRACT The community service activities in Talok Village aim to empower small-scale chicken farmers to support local food security and the achievement of the National Nutrition Master Plan (MBG). The method used is a participatory approach through problem identification, extension, training, demonstration, mentoring, and joint evaluation involving Golden Egg Farm (600 chickens) and Amanah Farm (500 chickens) as partners. The results of the activities showed an increase in egg productivity from 65% to 72% at Golden Egg Farm and from 60% to 68% at Amanah Farm, with a total contribution of around 23,160 eggs/month (139 kg of protein), feed cost efficiency of 15-17%, and a 3-4% reduction in mortality rates. In addition, farm waste was processed into ±45 kg of compost per month, while pre-test and post-test results showed an average knowledge increase of 33.1% in the areas of maintenance management, biosecurity, waste management, marketing, and food security. Thus, this programme has proven effective in enhancing farmers' capacity, producing a productive and environmentally friendly chicken farming model, and making a tangible contribution to the supply of animal protein in support of the SDGs, particularly zero hunger and good health and well-being. Keywords: Empowerment of chicken farmers; Food security; Poultry biosecurity; Farm waste management; Digital marketing of livestock products